Kritik terhadap Tindakan Glorifikasi Tubuh Perempuan dalam Dunia Perkontenan Perspektif Teologi Tubuh Yohanes Paulus II - Bano, Arkidius; Jani, Berno (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This paper aims to criticize the act of glorification of women’s bodies in the world of content from the perspective of Jhon Paul II’s theology of the body. This scientific study uses a descriptive qualitative method with basic data collection techniques using literature studies and in-depth observations. The data analysis techniqque uses steps according to Miles and Huberman, namely data reduction, data display and drawing conclusions. Based on the results of the analysis, it can be concluded that the world of content has a significant influence on the act of the glorification of women’s bodies. Women tend to show their bodies transparently in the world of social media content for the sake of self-glorification. The act of glorifying women’s bodies is a form of abuse of the body as a representation of God. The concept of Jhon Paul II’s thelogy of the body plays a significant role in re-awakening all humans, especially women, to respect, appreciate and uphold the dignity and meaning of their bodies as images and representations of God in the World.